First insights into Alternaria multi-toxin in vivo metabolism. (February 2019) - Puntscher, Hannes; Hankele, Svenja; Tillmann, Katharina; Attakpah, Eva; Braun, Dominik; Kütt, Mary-Liis; Del Favero, Giorgia; Aichinger, Georg; Pahlke, Gudrun; Höger, Harald; Marko, Doris; Warth, Benedikt
Graphical abstract: Highlights: First study exposing rats to a complex Alternaria toxin mixture. Several Alternaria toxins determined in rat urine and feces for the first time. Excretion rates for seven toxins estimated. Abstract: Alternaria mycotoxins frequently contaminate agricultural crops and may impact animal and human health. However, data on mammalian metabolism and potential biomarkers of exposure for human biomonitoring (HBM) are scarce. Here, we report the preliminary investigation with respect to metabolism and excretion of Alternaria toxins in Sprague Dawley rats. Four animals were housed in metabolic cages for 24 h after gavage administration of an Alternaria alternata culture extract containing ten known toxins. LC–MS/MS analysis of 17 Alternaria toxins in urine and fecal samples allowed to gain first insights regarding xenobiotic metabolism and excretion rates. Alternariol (6–10%), alternariol monomethyl ether (AME, 6–7%) and tenuazonic acid (up to 55%) were recovered in urine and fecal samples (9%, 87%, 0.3%, respectively), while perylene quinones administered at comparatively high levels, were either determined at very low levels (up to 0.5% altertoxin I in urine and 15% in feces; 0.2% alterperylenol in urine and 3% in feces) or not at all (altertoxin II, stemphyltoxin III). AME-3-sulfate, which was not present in the administered extract, was determined in urine, representing up to 23% of the AME intake. Critical evaluation of the applied sample preparation protocol and LC–MS/MS analysis revealed interesting preliminary results and information crucial for improving follow-up experiments.